Vloga farmacevta pri skrbi za ustno zdravje - Luštrik, Matevž (Farmacevtski vestnik, 2019)
The oral health care should be included in the adequate health and body care. The optimal oral health enables the normal food procession, communication and allows us to possess a fulfilled social life. It should be emphasized that the main contribution to the oral health consists of consistent oral hygiene, self-examination of the oral cavity and regular visits to the dentist. The paper briefly describes the conditions and treating the problems, referred to the oral health, which are commonly addressed to a community pharmacist during daily work with the patients and the frequently stated questions.
Keywords: občutljivi zobje; pekoč jezik; slab zadah; suha usta; uporaba fluoridov; Ustna higiena; vnetje dlesni